OBJECTIONS TO INDEX NUMBER ACCOUNTING. - Bowers, Russell (The Accounting Review, 1950)
Abstract Following the general price inflation rafter World War I there was much discussion about accounting errors in the measurement of business profit when conventional or legal dollars were used in reporting historical costs. This discussion reached a climax in 1936 with the appearance of Sweeney's Stabilized Accounting. Now that another wave of general price increase has swept over the country, the discussion has been resumed. The valid objections to the application of index numbers to accounting data for purposes of reporting profits and losses are few. Unless the general price level remains constant, better index numbers should be constructed. An index designed to measure the change in general purchasing power of the dollar is superior for this purpose to any more special index. The index ideally might be one based on all commodities, or it might be one based on the prices of consumer's goods. The use of index numbers gives recognition to the economic realities of a business situation in place of mere legal formality where legal dollars are assumed to have a constant purchasing power.